PENGARUH EMOTIONAL SPIRITUAL QOUTIENT BERDASARKAN RUKUN IMAN DAN RUKUN ISLAM TERHADAP ETOS KERJA ISLAMI KARYAWAN RS. PKU MUHAMMADIYAH SURAKARTA - Santosa, Mulato Santosa (Jurnal Analisis Bisnis Ekonomi, 2005)
Entering globalization era nowdays, competition progressively tighen. Tight competition be at all level, start the interracial competition, multinational intercompany competition. In Surakarta, local intercompany competition including hospital progressively tighten. This matter is seen from various repair of facility and service at pain which there have. This competition increase to tighten with the appearance of various new hospital. Ethos work the human resources represent one of key for make-up quality of nation and also company. High job ethos yield pre-eminent company or nation capable to win the competition. Ethos work the Indonesia human resources still be left behind other state. Ethos work a nation influenced by embraced confidence. Indonesian nation which majority believe in the Islam hence to increase ethos work the human resources to win competition have to use the method of Islam approach. The research is to know the influence of emotional spiritual quotient pursuant to foundation believe and Islam Foundation to Islamic ethos work of employees Hospital PKU Muhammadiyah of Surakarta. Result showed that, emotional spiritualn quetient pursuant to foundation believe and Islam foundation influence positive and significanto Islamic ethos work employee Hospital PKU Muhammadiyah of Surakarta.